Isolasi dan Uji Resistensi Bakteri Endofit Eceng Gondok Terhadap Krom - Nurmalasari, Ade; Oedjijono, Oedjijono; Lestari, Sri (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Endophytic bacteria are bacteria that live in plant tissues and are not pathogenic to the host. One of endophytic bacterial host is water hyacinth. Water hyacinth could accumulate heavy metals, one of which is chrome. The purpose of this study was to obtain endophytic bacteria of water hyacinth (Eichhornia crassipes Mart.), to identify the endophytic bacteria of water hyacinth, and to determine the resistance of endophytic bacteria of water hyacinth to Chrome (Cr). The research method used was a survey with a purposive random sampling technique. Stages of research include root sampling, sterilization of root samples using 2% NaOCl3, isolation of water hyacinth endophytic bacteria on agar nutrient medium (NA), characterization of bacterial endophytes and resistance test of water hyacinth bacteria to chromium. Based on the results of the study, 8 isolates of endophytic bacteria were isolated from the roots of water hyacinth. Based on Bergey's Manual Determinative of Bacteriology, 6 bacterial isolates (E1, E2, E3, E5, E6, E8) were identified as Bacillus and 2 isolates (E4, E7) were identified as Pseudomonas. All water hyacinth endophytic bacteria obtained were resistant to chromium to a concentration of 750 mg/L.